A Review on Sliding Wear Behaviour of Aluminium Matrix Composites with Hybrid Reinforcements for Automotive Applications - Jaswinder Singh (Japanese Society of Tribologists, 2014)
The aluminium matrix composites, particularly with hybrid reinforcements are the advanced materials that have been widely used as a substitute material in the transport sector, to manufacture lighter-weight and higher-performance components. As these components are often subjected to sliding wear under working conditions, therefore several of these applications require enhanced frictional and wear resistance. The purpose of the current review is therefore aimed at highlighting the focus of the current research scenario, in the field of tribological behaviour of aluminium based hybrid composites, to explore the materials for automotive applications. A significant experimental data has been reported in this area, and it has been revealed that the materials possessing high wear resistance are associated with formation of a stable tribolayer on the wear surface and the fine equiaxed wear debris. The operating variables such as applied load, sliding distance and sliding speed, temperature, wearing surface hardness, reinforcement contents and morphology have been found as critical parameters in relation to the wear regime, encountered by the material during operation. An attempt has been made to present and review the various aspects relevant to sliding wear behaviour of aluminium alloys and the hybrid composites, with different combinations of reinforcements. Further, it has been found that the cost and the weight of the aluminium matrix composites can be considerably controlled, by addition of hybrid reinforcements, without compromising the tribological properties.